Four-year mortality by some socioeconomic indicators: the Oslo study. Issue 1 (March 1980) - Holme, I; Helgeland, A; Hjermann, I; Leren, P; Lund-Larsen, P G
Abstract : The association between four-year mortality and some socioeconomic indicators has been studied in al Oslo men aged 40–49, invited to a screening programme for cardiovascular disease, and in a 'healthy' subgroup of participating men free of cardiovascular disease and diabetes at screening. The lowest social class exhibited a much higher total mortality than the other classes. This was pronounced for a variety of causes of death, such as cancer of the lung, accidents and homicide, and coronary heart disease. The negative mortality gradient by increasing socioeconomic status can to a certain degree be 'explained' by the coronary risk factor pattern.